DNA Methylation Fluctuation Induced by Virus Infection Differs between MD-resistant and -susceptible Chickens - Luo, Juan; Yu, Ying; Tian, Fei; Zhang, Huanmin; Chang, Shuang; Song, Jiuzhou (Frontiers in Genetics, 2012)
Marek’s disease (MD) is a lymphoproliferative disease induced by Marek’s disease virus (MDV) infection. To augment vaccination measures in MD control, host genetic resistant to MD becomes obviously more and more important. To elucidate the mechanism of MD-resistance, most of researches were focused on the genetic differences between resistant and susceptible chickens. However, epigenetic features between MD resistant and susceptible chickens are poorly characterized. Using bisulfite pyrosequencing method, we found some candidate genes have higher promoter methylation in the MD-susceptible (L72) chickens than in the MD-resistant (L63) chickens. The hypermethylated genes, involved in cellular component organization, responding to stimulus, cell adhesion, and immune system process, may play important role in susceptibility to disease by deregulation of these genes. MDV infection induced the expression changes of all three methyltransferases genes (DNMT1, DNMT3a, and DNMT3b) in both lines of chickens. The DNMT1 was up-regulated in L72, whereas the DNMT3b was down-regulated in L63 at 21 dpi. Interestingly, a dynamic change of promoter methylation was observed during MDV life cycle. Some genes, including HDAC9, GH, STAT1, CIITA, FABP3, LATS2, and H2Ac, showed differential methylation behaviors between the two lines of chickens. In summary, the findings from this study suggested that DNA methylation heterogeneity and MDV infection induced methylation alterations differences existed between the two lines of chickens. Therefore, it is suggested that epigenetic mechanisms may be involved in modulating the resistance and/or susceptibility to MD in chickens.